Feasibility study on the implementation of optimized production technology in a manufacturing company by simulationmodelling - Izadifar, Mozhgan (2013)
Optimized Production Technology, which is later known as Theory of Constraint, as a profit making technique has been reviewed carefully. According to the theory, each system has at least one bottleneck or constraint that controls the whole system’s behavior. Based on this theory, this thesis aims to study the method of implementing Optimized Production Technology with the aid of the Arena simulation software to check the feasibility of this method in a manufacturing company. This study provides a simulation model of a manufacturing production line as an initial step of defining the bottleneck of the system. Then a number of scenarios are discussed related to the evaluated bottlenecks that offer the implementation of Optimized Production Technology and in the system to obtain the most optimized improvement in terms of cost and throughput. These improvements will help the company to achieve more benefit as well as improvements in the total throughput number. In order to make a general comparison between the improvements made and the current state of the system of manufacturing production line, the sufficient performance measurements has been proposed as well. The best scenario to improve the system is to reduce all the three bottlenecks at the same time.